Site-Specific Protein Labeling Methods and Protocols - Gautier, Arnaud.; Gautier, Arnaud.; Hinner, Marlon J.; Hinner, Marlon J. (Methods in Molecular Biology,, 2015)
This detailed volume provides in-depth protocols for protein labeling techniques and applications, with an additional focus on general background information regarding the design and generation of the organic molecules used for the labeling step. Chapters present a comprehensive overview on the most relevant and established labeling methodologies, and help researchers to choose the most appropriate labeling method for their biological question. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Site-Specific Protein Labeling: Methods and Protocols is designed to help scientists from all fields to get a better understanding of labeling techniques.